2007
DOI: 10.1038/nature05490
|View full text |Cite
|
Sign up to set email alerts
|

Basis for a ubiquitin-like protein thioester switch toggling E1–E2 affinity

Abstract: Ubiquitin-like proteins (UBLs) are conjugated by dynamic E1-E2-E3 enzyme cascades. E1 enzymes activate UBLs by catalysing UBL carboxy-terminal adenylation, forming a covalent E1 throught UBL thioester intermediate, and generating a thioester-linked E2 throught UBL product, which must be released for subsequent reactions. Here we report the structural analysis of a trapped UBL activation complex for the human NEDD8 pathway, containing NEDD8's heterodimeric E1 (APPBP1-UBA3), two NEDD8s (one thioester-linked to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
293
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(304 citation statements)
references
References 35 publications
(26 reference statements)
11
293
0
Order By: Relevance
“…6B and data not shown). It has been found that an E1-E2 transthiolation event requires significant conformational rearrangements of the E1 enzyme (31,34,35). Crystallography studies with the NAE ternary complex and Ubc12 show that the core domain of Ubc12 associates with the UFD of NAE and a peptide-like extension on Ubc12 docks into a groove in the adenylation domain, adjacent to the ATP-binding site on NAE (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6B and data not shown). It has been found that an E1-E2 transthiolation event requires significant conformational rearrangements of the E1 enzyme (31,34,35). Crystallography studies with the NAE ternary complex and Ubc12 show that the core domain of Ubc12 associates with the UFD of NAE and a peptide-like extension on Ubc12 docks into a groove in the adenylation domain, adjacent to the ATP-binding site on NAE (35).…”
Section: Discussionmentioning
confidence: 99%
“…Crystallography studies with the NAE ternary complex and Ubc12 show that the core domain of Ubc12 associates with the UFD of NAE and a peptide-like extension on Ubc12 docks into a groove in the adenylation domain, adjacent to the ATP-binding site on NAE (35). It is hypothesized that formation of NEDD8-adenylate on the NAEϳNEDD8 thioester induces a rotation in the UFD domain of almost 120°, which enables NAE to bind Ubc12 and align it in prime position for transthiolation (35). After the NEDD8 thioester is transferred to Ubc12, the loss of the covalent bond with NEDD8 induces the UFD of NAE to rotate back (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the transfer of Ublp from E1 to E2, the E2 enzyme is recruited to the E1-SUMO thioester conjugate by binding to multiple sites on E1, including the Cys domain (the domain containing the active Cys residue) and the ubiquitin-like (Ubl) domain (10,11). Among these multiple binding sites, the Ubl domain has the highest binding affinity, and thus it is the key E2-binding site.…”
mentioning
confidence: 99%